Patanda Kadupipi dan Pergulatan Nilai Kristiani: Sebuah Kajian Pendidikan Agama Kristen Kontekstual dalam Pernikahan Adat Sumba Timur - Waworuntu, Hanry Donald (Jurnal Apokalupsis, 2025)
This study aims to analyze the Patanda Kadupipi tradition in the customary marriage practices of the Kambera community in East Sumba in relation to Christian teachings, and to formulate a contextually relevant concept of Christian Religious Education to guide the Christian community in responding to this tradition. This research employs a qualitative method using interviews and literature review to evaluate the Patanda Kadupipi tradition in the light of contextual Christian Religious Education (CRE). The findings indicate that the practice of cohabitation prior to church marriage blessing within the Patanda Kadupipi tradition creates a tension of values between customary traditions and Christian teachings that emphasize the sanctity of marriage. Contextual and culturally sensitive Christian Religious Education plays a crucial role in addressing this conflict through dialogical and transformational approaches. In conclusion, contextual Christian Religious Education not only embraces culture but also navigates local values in the light of the Gospel—affirming what is compatible and transforming what is contradictory—in order to foster authentic and responsible faith formation within the East Sumba community.